2014
DOI: 10.1139/cjm-2013-0792
|View full text |Cite
|
Sign up to set email alerts
|

Soybean fungal soil-borne diseases: a parameter for measuring the effect of agricultural intensification on soil health

Abstract: The aim of this study was to investigate the influence of agricultural intensification on soil microbial diversity, chemical and physical parameters, and the decrease of the incidence of sudden death syndrome (Fusarium crassistipitatum) and charcoal rot (Macrophomina phaseolina) in soybean. Soils under different management systems were evaluated during 2 crop cycles: soybean monoculture for 24 and 11 years, soybean-maize rotation for 15 and 4 years, 1 year of soybean, and native vegetation. The incidence of bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…As previously suggested (Pérez-Brandán et al, 2014), there is a positive effect of Trichoderma on the greater diversity of plant species, confirmed in the present work in the ASP treatment. Soil moisture is also known to be an important factor influencing Trichoderma spp.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…As previously suggested (Pérez-Brandán et al, 2014), there is a positive effect of Trichoderma on the greater diversity of plant species, confirmed in the present work in the ASP treatment. Soil moisture is also known to be an important factor influencing Trichoderma spp.…”
Section: Resultssupporting
confidence: 92%
“…and Trichoderma spp. in each soil sample were estimated by dilution plating on agar (Pérez-Brandán et al, 2014). An aliquot of 10 g of soil was diluted in 90 mL of sterile distilled water and stirred for 90 minutes at 170 rpm on an orbital flask shaker.…”
Section: Fusarium and Trichoderma Densitymentioning
confidence: 99%
“…), which act as biological control agents against soil-borne pathogens (e.g., Fusarium spp.) [108,109]. Similarly, some studies have also reported that long-term CC may also decrease the microbial biomass P [110] and C contents [111].…”
Section: Microbial Biomass or Abundancementioning
confidence: 86%
“…In order to increase yield, continuous investment in modern soil management technologies, liming, fertilization, and seeding, associated with efficient weed, pest and disease control is needed (THOMAS & COSTA, 2010;FREITAS, 2011), in addition to suitable crop rotation. Expansion of soybean growing area has prompted an increase in monoculture farming (PEREZ-BRANDAN et al, 2014); thereby, raising the occurrence and intensity of diseases. All parts of the soybean plant are susceptible to plant pathogens (HARTMAN et al, 1999), especially fungus-related diseases associated with root rot (RR) (HENNING, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…* Corresponding author. : soybean-oat+soybean-oat, soybean-maize+soybean-maize, soybean-wheat+soybean-wheat and soybean-pasture+soybean-pasture BRANDAN et al, 2014;KLINGELFUSS et al, 2007). Root rot and early plant death (COSTAMILAN, 1999;SARR et al, 2014) affect pod filling, resulting in small, green or deteriorated seeds that compromise seed lot quality and reduce crop yield (SHADAKSHARI et al, 2014).…”
Section: Introductionmentioning
confidence: 99%